Implementación de la inteligencia artificial en la creación de recursos digitales, en la catedra de estudios sociales para el sexto grado en la unidad educativa intercultural bilingüe Surupucyu, en el periodo académico octubre 2023-febrero 2024. - Alex David, Arevalo Agualongo (2024)
This project focused on the strategic integration of artificial intelligence in the educational process to enhance the creation of digital resources in the Surupucyu Bilingual Intercultural Unit of Guanujo, in the Guaranda canton, in the Bolívar Province. We explore how artificial intelligence can enrich educational content, personalizing and adapting to resources, to optimize the understanding of complex topics in the social area. We focus on developing intelligent tools that transform the way students access, interact and absorb knowledge. Through the use of technological tools we generate dynamic and contextualized digital resources that promote more interactive, attractive and effective learning. Most importantly, improving the quality and effectiveness of social studies teaching, using artificial intelligence as a powerful ally to create illustrative videos that adapt to the individual needs of students, thus fostering greater engagement and understanding of concepts. fundamental in this area. Finally, a guide is presented for the development of educational videos based on artificial intelligence through the application of Fliki and D-id, this is advantageous since teachers will implement this innovative technological project in all areas of knowledge, which would energize the environment. educational, with the incorporation of new teaching-learning methodologies that favor the development of skills in students, particularly analytical skills that enable them to use artificial intelligence effectively in various situations and study spaces